Phacoemulsification Cataract Extraction in Patients with Fuchs' Heterochromic Iridocyclitis - Ahmed M. Bawazeer, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Fuchs heterochromic iridocyclitis commonly presents with chronic mild uveitis with predisposition to cataract and glaucoma. There are inherent risks of major intra and postoperative complications in uveitic cataracts. The aim was to evaluate the efficacy of phacoemulsification surgery with acrylic foldable intraocular lens in patients with Fuchs heterochromic iridocyclitis. Thirteen eyes of 12 patients were analyzed with Fuchs' heterochromic iridocyclitis with cataracts who underwent phacoemulsification with in-the-bag foldable intraocular lens implantation. The mean follow up was 7.5 months. All patients had postoperative visual acuity better than 20/25 (p < 0.00023). All of them had quite intra and post operative periods without major post operative complications. One patient developed transient cystoid macular edema which resolved with topical steroids. Phacoemulsification with hydrophobic acrylic IOL is the safe technique of cataract removal in patients with Fuchs heterochromic Uveitis.